Computer simulation of food sterilization using an alternating direction implicit finite difference method - Mohamed, Ibrahim O. (undefined, 2003)
A computer simulation model for food sterilization was developed based on the solution of Fourier's heat conduction equation for finite cylindrical geometry. The solution is based on the alternating direction finite difference method. Experimental verification of the model was performed using two sets of published data, which shows good agreement with the simulation results. Furthermore, the model performance was tested by subjecting a constant retort temperature profile to an upset condition, the model responded quite well indicting its potential for investigating the influence of constant retort temperature upset conditions on lethality and the effects of variable retort temperature profiles on quality retention and process optimization. In addition, the model can also be used for process control. © 2003 Elsevier Ltd. All rights reserved.